TECHNOLOGY ACCEPTANCE IN EFL LEARNING: WORKING STUDENTS’ PERCEIVED USEFULNESS AND EASE - Nais Saraswati; Fatimah Tuzahra (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
The integration of technology has become indispensable in higher education and has been intensified by the migration to online learning post COVID-19 pandemic. This study explores the perspective of English Foreign Language (EFL) full-time working students on the usefulness (PU) and perceived ease of use (PEOU) of Information and Communication Technology (ICT) integration in online learning settings under the Technology Acceptance Model (TAM) framework. Using a qualitative case study design, three purposively selected participants were chosen from a population of 60 students based on their employment status and digital literacy. A short questionnaire was used solely to collect demographic and background information, while the main data were derived from structured interviews and digital artifacts. All data were analyzed using constructivist grounded theory through open and axial coding methods. The findings underscore that ICT integration provides flexibility, efficiency, and autonomy, encouraging students to balance both academic and professional responsibilities while improving students’ motivation and performance, and fostering problem-solving skills. Multimodal resources and AI tools provide merits for participants as they support self-directed learning. However, challenges persist, such as unstable internet connections, limited LMS usability, and insufficient technical training hindered effectiveness.